Adipose-Derived Mesenchymal Stem Cell (AD-MSC)-Like Cells Restore Nestin Expression and Reduce Amyloid Plaques in Aluminum Chloride (AlCl3)-Driven Alzheimer's Rat Models - Annita, Annita; Revilla, Gusti; Ali, Hirowati; Almurdi, Almurdi (Cell and BioPharmaceutical Institute, 2024)
Background: Alzheimer's disease (AD) is a neurodegenerative disorder with a significant burden on public health, and current treatments offer limited efficacy. This study investigated the effectiveness of adipose-derived mesenchymal stem cells (AD-MSCs) on the expression of the nestin gene and amyloid plaque in an aluminum chloride (AlCl3)-driven Alzheimer's rat model.Materials and methods: AD-MSCs were characterized using flow cytometry. Adult male Wistar rats were treated with/without AlCl3 and injected with/without AD-MSCs. After 5 days of AlCl3 ingestion and 4 weeks of subsequent AD-MSCs intraperitoneal injection, behavioral and molecular assessments were conducted. The Y-maze alternation test was used to test spatial learning of rats. Nestin gene expression was evaluated using reverse transcription-quantitative polymerase chain reaction (RT-qPCR). The presence of amyloid plaque in the cortex and the hippocampus was evaluated through Congo red staining.Results: AD-MSC-like cells expressed the MSC markers CD90, CD73 and CD105. The Y-maze alternation result for rats treated with AlCl3 and AD-MSC-like cells was significantly higher compared with rats treated with AlCl3 only. Nestin gene expression was significantly higher in rats treated with AlCl3 and AD-MSC-like cells compared to those treated with AlCl3 only. After AD-MSC-like cells treatment, the Congo red staining results of rat’s cortex and hippocampus were significantly decreased.Conclusion: The findings suggest that AD-MSC-like cells possess therapeutic potential in restoring neural plasticity, amyloid plaque clearance and warrant further investigation for AD treatment. This study contributes to the emerging field of stem cell therapy for neurodegenerative diseases by highlighting the promise of AD-MSCs.Keywords: Alzheimer's disease, adipose-derived mesenchymal stem cells, neural plasticity, congo red staining, stem cell therapy